A study of the chemical composition of wet precipitation, particulate matter (PM2.5) and total suspended particulate in Singapore. - Tiong, Diane Ling Ying. (2013)
A comprehensive one-year study on the rainwater and particulate matter in ambient air of Singapore was performed and reported in this thesis. The rainwater composition and monthly trends were analyzed with the use of various analytical techniques, which includes Ion-chromatography and Inductively-Coupled Plasma Mass Spectrometry (ICP-MS). The pH and electrical conductivity (EC) of the rainwater collected were monitored concurrently as it has a close relation to the PSI index reported by the National Environmental Agency (NEA) of Singapore. The rainwater samples were collected in both sites, NTU and Hougang. These two sites have different distinctive environment. NTU, located in the western part of Singapore is surrounded with industries and refineries, which contribute pollutants to the atmosphere. Whereas, Hougang is a residential area with minimal industrial activities, however, the sampling site is close to the main road with moderate to heavy traffic. It was found in this study that the rainwater collected in NTU is high in content for trace metals related to refineries and industrial activities whereas rainwater samples collected in Hougang contain trace metals related to traffic. The pH of the rainwater samples collected in NTU is lower than Hougang with an averaged pH of 4.53 and 4.61 respectively. The higher averaged pH collected in Hougang would suggest the presence of less acidic ions present in the rainwater which is responsible for acid rain. The acidic ions contained in rainwater can be attributed to the release of SOx and NOx by industries located in the western part of Singapore where NTU is in close proximity to Jurong Island and Tuas.